2017
DOI: 10.1128/mbio.00186-17
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Alginate Overproduction Promotes Coexistence with Staphylococcus aureus in a Model of Cystic Fibrosis Respiratory Infection

Abstract: While complex intra- and interspecies microbial community dynamics are apparent during chronic infections and likely alter patient health outcomes, our understanding of these interactions is currently limited. For example, Pseudomonas aeruginosa and Staphylococcus aureus are often found to coinfect the lungs of patients with cystic fibrosis (CF), yet these organisms compete under laboratory conditions. Recent observations that coinfection correlates with decreased health outcomes necessitate we develop a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
201
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(214 citation statements)
references
References 68 publications
(102 reference statements)
9
201
2
2
Order By: Relevance
“…Previously, it has been shown that nonmucoid PAO1 kills S. aureus lab isolate JE2, while mucoid PAO1 does not [13]. Therefore, we were curious whether this trend would be maintained with CF clinical isolates of S. aureus and consequently all of our 65 S. aureus isolates were assessed in a coculture assay with both nonmucoid and mucoid PAO1.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously, it has been shown that nonmucoid PAO1 kills S. aureus lab isolate JE2, while mucoid PAO1 does not [13]. Therefore, we were curious whether this trend would be maintained with CF clinical isolates of S. aureus and consequently all of our 65 S. aureus isolates were assessed in a coculture assay with both nonmucoid and mucoid PAO1.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, we were curious whether this trend would be maintained with CF clinical isolates of S. aureus and consequently all of our 65 S. aureus isolates were assessed in a coculture assay with both nonmucoid and mucoid PAO1. While a number of different techniques have been used to look at how P. aeruginosa and S. aureus survive in coculture [13, 51-55], we have developed a simple, repeatable, well-controlled, quantitative assay for monitoring these interactions in vitro . This coculture assay allows for these bacteria to come in contact with one another on a solid surface as they might in a biofilm in the lung.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of interactions between S. aureus and P. aeruginosa could be observed with CF patient isolates: the well-described competitive phenotype, where P. aeruginosa inhibits S. aureus growth, 16 and the newly described phenotype of coexistence, where P. aeruginosa is unable to outcompete S. aureus 1921 . In order to quantify the importance of this last phenotype, we collected 50 pairs of S. aureus and P. aeruginosa from 36 co-infected CF patients.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on P. aeruginosa populations isolated from individual lungs, have demonstrated divergent evolution, resulting in heterogeneous populations of P. aeruginosa within patients (16,17,19). This genetic adaptation and diversification is likely to impact on levels of pathogenicity and the efficacy of antibiotic treatment (16,20), and could potentially impact how other species of microbe colonize the CF lung (4,(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%